2020
DOI: 10.1111/sms.13626
|View full text |Cite
|
Sign up to set email alerts
|

Altered hip control during a standing knee‐lift test is associated with increased risk of knee injuries

Abstract: A few prospective studies have investigated hip and pelvic control as a risk factor for lower extremity (LE) injuries. The purpose of this study was to investigate whether deficits in hip and lumbopelvic control during standing knee‐lift test are associated with increased risk of acute knee and LE injuries in youth team sports. At baseline, 258 basketball and floorball players (aged 12‐21 years) participated in a standing knee‐lift test using 3‐dimensional motion analysis. Two trials per leg were recorded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…A video analysis study of ACL injuries during single-leg movements showed that the trunk lateral tilt angles of ACL-injured female athletes were 31 larger than those of control female athletes (Hewett, Torg, & Boden, 2009). There was a significant association between a large pelvic lateral tilt angle and ACL injury risk in female athletes (Leppänen et al, 2020). The present study showed that landing instructions are effective in reducing pelvic and trunk lateral tilt.…”
Section: Discussionsupporting
confidence: 44%
“…A video analysis study of ACL injuries during single-leg movements showed that the trunk lateral tilt angles of ACL-injured female athletes were 31 larger than those of control female athletes (Hewett, Torg, & Boden, 2009). There was a significant association between a large pelvic lateral tilt angle and ACL injury risk in female athletes (Leppänen et al, 2020). The present study showed that landing instructions are effective in reducing pelvic and trunk lateral tilt.…”
Section: Discussionsupporting
confidence: 44%
“…metaanalysis, best evidence synthesis). Risk factors reported by a single study are presented in Electronic Supplementary Material Appendix S3 [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Risk Factor Synthesismentioning
confidence: 99%
“…Potential participant heterogeneity was accounted for by limiting studies to team field and court sports with similar physical demands, and performing random effect model meta-analyses. Further, this review focussed on synthesising evidence across studies, however, there were a number of risk factors found by single studies that require further examination [68,40,42,70,56,35,32].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Altered hip control of increased contralateral pelvic hike (hitch) is associated with increased risk of acute non-contact knee injuries and anterior cruciate ligament (ACL) injuries. 59 . This is a test of specific muscle recruitment/ concentric activation of the hip flexor stabilizers (iliacus/pectineus) 7 , 49 and assesses the ability to actively dissociate and control hip lateral rotation/abduction 26 .…”
Section: Standing Hip Flexion Test (Flex 0-110 )mentioning
confidence: 99%